Rafael Francisco Osejo: A Man of Science from His Time? - Amador, Jorge A. (2022)
The construction of today's societies has been possible thanks to the contributions of numerous characters to politics, economics, the arts, and sciences. Considered one of the actors in the process of independence of Costa Rica, the Bachelor Rafael Francisco Osejo had a prolific life as a politician, educator, and lawyer, however, there is relatively little that is known about his contribution to the development of a science of his time. Here his writings are analyzed in the tenor of the science of the period to answer the question: Was Osejo a man of science of his time? His two main works related to topics such as seismology, astronomy, mathematics, physics, and meteorology are examined and discussed, investigating as a complement to the contents of some of the works that this character had in his library. Osejo was a very well-informed and educated character in the scientific knowledge of his time. As a man of science, he achieved an active personal and institutional participation at the beginning of a relevant scientific era in the country.